2018
DOI: 10.1371/journal.pone.0196079
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3-hydroxybutyrate) production in an integrated electromicrobial setup: Investigation under stress-inducing conditions

Abstract: Poly(3-hydroxybutyrate) (PHB), a biodegradable polymer, can be produced by different microorganisms. The PHB belongs to the family of polyhydroxyalkanoate (PHA) that mostly accumulates as a granule in the cytoplasm of microorganisms to store carbon and energy. In this study, we established an integrated one-pot electromicrobial setup in which carbon dioxide is reduced to formate electrochemically, followed by sequential microbial conversion into PHB, using the two model strains, Methylobacterium extorquens AM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 32 publications
1
16
1
Order By: Relevance
“…[23] Furthermore, it has to be mentioned that contrary to the results reported by Al Rowaihi et al, within this study the conversion of formate to PHB could also be shown without the application of electrolysis and the consequently assumed presence of reactive oxygen species. [23] However, when evaluating the PHB concentration, the starting biomass concentration and substrate availability also have to be taken into account. It is assumed that with a higher amount of resting cells and constant substrate feed significantly higher product concentrations are feasible.…”
Section: Cultivation Of C Necator On Formate Mediumcontrasting
confidence: 89%
See 1 more Smart Citation
“…[23] Furthermore, it has to be mentioned that contrary to the results reported by Al Rowaihi et al, within this study the conversion of formate to PHB could also be shown without the application of electrolysis and the consequently assumed presence of reactive oxygen species. [23] However, when evaluating the PHB concentration, the starting biomass concentration and substrate availability also have to be taken into account. It is assumed that with a higher amount of resting cells and constant substrate feed significantly higher product concentrations are feasible.…”
Section: Cultivation Of C Necator On Formate Mediumcontrasting
confidence: 89%
“…[12,19] When combining electroreduction to form intermediates with bioproduction, different approaches are feasible (Scheme 1). One promising option are secondary microbial electrochemical technologies (MET), locating the initial electrochemical reduction in-situ to the microbial biosynthesis, [20,21] as it has already been shown for formate [22,23] and H 2 . [24] However, scale-up issues and non-ideal conditions of the electrochemical set up pose major challenges for establishing in-situ production with direct bioconversion in industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…14). These dots are reminiscent of the polyhydroxyalkanoate storage granules that some bacterial species produce under conditions where their growth is unbalanced (56,57) or when cells are otherwise stressed (58,59). It is also possible that these dots comprise the nucleoid or some other remnant of a leaky cytoplasm.…”
Section: Elevated Cell Mortality In the Population That Evolved To Grmentioning
confidence: 99%
“…More recently, the scientific community revealed the significant protective role of PHA against a number of stress factors, which are harmful or even lethal for PHA-free microbial cells (53). In this context, it was demonstrated that presence of PHA exerts a protective effect against the impact of elevated temperature (54), attenuates the destructive impact of excessive UV-irradiation by scattering light (55), helps to repair damage caused by repeated freezing-and-thawing cycles (56) or sudden osmotic imbalances (57), and elevates the burdens caused by chemical oxidants in general (58), and by sudden generation of reactive oxygen species (ROS) in particular (59). Regarding elevated salt concentrations (hyperosmotic conditions), presence of PHA granules in living microbes turned out to support the cells to better survive the harmful effects of osmotic up-shock; this also clarifies why PHA granules are found in so many haloarchaeal species isolated up to date from extremely saline ecological niches (57).…”
Section: Conversion Of Renewable Biomass To Convertible Substrates (Umentioning
confidence: 99%